We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
111
3
avatar

X^2 -2XY +Y^2=36 so X-Y =?

 

 

My solution:(Not so sure...)

X^2 -2XY +Y^2=(X - Y)^2

Therefore, (X - Y)^2=36 So, X-y=6

But it is also a choice question and here are the choices:

6

+-6 (Postive or negative six) (could it be?)

-6

18.

 

 

Thank you in advance!

 Apr 30, 2019
 #1
avatar+28134 
+1

The +- solution is correct.

 Apr 30, 2019
 #2
avatar
0

How ?,how could i know 

Guest Apr 30, 2019
 #3
avatar+103121 
0

If    x - y  = 6   then   (x - y)^2  = ( 6 )^2  = 36

 

If  x - y  = - 6 then  (x - y)^2  = (-6)^2  = 36

 

 

 

cool cool cool

 Apr 30, 2019

28 Online Users

avatar
avatar
avatar
avatar
avatar